Completeness and registration bias in PROCARE, a Belgian multidisciplinary project on cancer of the rectum with participation on a voluntary basis. Issue 9 (June 2015) - Jegou, D.; Penninckx, F.; Vandendael, T.; Bertrand, C.; Van Eycken, E.; PROCARE, 1
Abstract Background PROCARE, a Belgian multidisciplinary project on rectal cancer, started in 2006 with participation on a voluntary basis. Completeness and bias of registration in PROCARE were assessed. Methods Data from 6353 patients with rectal cancer were extracted from the population based Belgian Cancer Registry for the period 2006–2008. Registration bias was studied by comparing patient, tumour and treatment characteristics of cases registered and non-registered in PROCARE. Relative survival (RS) of patient subgroups was analysed. Results PROCARE included 37% of all Belgian rectal cancer patients. Registration was highly variable between participating centres which recorded on average 56% of their patients. Significant differences in patient, tumour and treatment related characteristics were observed between registered and non-registered patients. The 5-year RS was 77% (95% confidence interval (CI): 74–80%) for registered patients and 56% (95% CI: 53–59%) for non-registered patients. After adjustment for patient, tumour characteristics and volume of centre, the relative excess risk of dying (RER) between registered and non-registered patients was 2.15 (95% CI: 1.85–2.50, p < 0.001). The 5-year RS of patients treated in centres that never participated in the project was 59% (95% CI: 55–63%) and, after adjustment, the RER was 1.16 (95% CI: 1.00–1.35, p < 0.050) compared to patients of the participating centres. Conclusion Registration of PROCARE patient data was incomplete, biased and variable between centres. Participation on a voluntary basis should be avoided for further projects. Quality assurance on a centre level requires compulsory and complete registration with a minimal but relevant data set for all patients treated in all centres.